2010
DOI: 10.1111/j.1365-2966.2009.16057.x
|View full text |Cite
|
Sign up to set email alerts
|

AINUR: Atlas of Images of NUclear Rings

Abstract: We present the most complete atlas of nuclear rings to date. We include 113 rings found in 107 galaxies, six of which are elliptical galaxies, five are highly inclined disc galaxies, 18 are unbarred disc galaxies, and 78 are barred disc galaxies. Star-forming nuclear rings occur in 20% of disc galaxies with types between T=-3 and T=7. We aim to explore possible relationships between the size and morphology of the rings and various galactic parameters. We produce colour index and structure maps, as well as Halp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
294
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(343 citation statements)
references
References 179 publications
(406 reference statements)
48
294
0
1
Order By: Relevance
“…After analysing broad band images, as in Paper I, and also the HST images published in the literature (e.g. Comerón et al 2010), we have also seen that this region coincides with changes in the morphology. Therefore, the bulge end defined using the kinematics is almost always coincident with the end of the nuclear structure: nuclear ring, double bar, inner spiral, etc., found in the broad-band images.…”
Section: Sample Characterisationmentioning
confidence: 99%
“…After analysing broad band images, as in Paper I, and also the HST images published in the literature (e.g. Comerón et al 2010), we have also seen that this region coincides with changes in the morphology. Therefore, the bulge end defined using the kinematics is almost always coincident with the end of the nuclear structure: nuclear ring, double bar, inner spiral, etc., found in the broad-band images.…”
Section: Sample Characterisationmentioning
confidence: 99%
“…In contrast, small bulges of late-type spirals are reminiscent of disks (see the reviews by Kormendy 1993;Wyse et al 1997;Kormendy & Kennicutt 2004). Some of them have a quite complex structure and host nuclear rings (see Buta 1995;Comerón et al 2010, for a compilation), inner bars (see Erwin 2004, for a list), and embedded disks (e.g., Scorza & Bender 1995;van den Bosch et al 1998;Pizzella et al 2002). Although the kinematical properties of many bulges are well described by dynamical models of oblate ellipsoids that are flattened by rotation with little or no anisotropy (Kormendy & Illingworth 1982;Davies & Illingworth 1983;Fillmore 1986;Corsini et al 1999;Pignatelli et al 2001;Cappellari et al 2006), the twisting of the bulge isophotes (Lindblad 1956;Zaritsky & Lo 1986) and the misalignment between the major axes of the bulge and disk (Bertola et al 1991;Varela et al 1996;Méndez-Abreu et al 2008) observed in several galaxies cannot be explained if the bulge and disk are both axisymmetric.…”
Section: Intrinsic Shape Of Disk Galaxiesmentioning
confidence: 99%
“…In this Section we compare the simulation to three early-type disc galaxies where previous study has shown the existence of distinct, moderately large NDs and/or massive stellar nuclear rings (which could plausibly be the most visible signature of an extended ND) inside bars (Erwin & Sparke 1999;Erwin et al 2003;Erwin 2004;Nowak et al 2010;Comerón et al 2010). Further details concerning the NDs, including their relation to the central bulges, can be found in Erwin et al (2014).…”
Section: Photometric Comparisonsmentioning
confidence: 99%
“…Labels indicate features corresponding to the inner and outer nuclear rings and the bar in the simulation ("inner NR", "outer NR", "bar"), along with the classical bulge, nuclear ring, and bar in NGC 4371 ("classical bulge", "NR", "bar"). liptical stellar nuclear ring with a radius of ≈ 10.5 ′′ (860 pc); there is little evidence for dust except in the very innermost (r < 1 ′′ ) regions and no evidence for current star formation, though the stellar nuclear ring is somewhat blue (Erwin & Sparke 1999;Comerón et al 2010). The bar is aligned almost along the minor axis of the projected disc; the outer isophotes have an ellipticity of ≈ 0.45, indicating an inclination of i ≈ 58 • (assuming the disc has an intrinsic thickness of c/a = 0.2, typical for S0 galaxies (Lambas, Maddox & Loveday 1992;Padilla & Strauss 2008;Rodríguez & Padilla 2013)).…”
Section: Comparison To Ngc 4371mentioning
confidence: 99%